Pengaruh Keterampilan Proses dalam Pembelajaran Berstrategi Student Team Heroic Leadership dengan Tugas Terstruktur terhadap Hasil Belajar Siswa - Luqy Barlanty Nafisah; Mohamad Anas (JURNAL PENDIDIKAN MATEMATIKA, 2018)
This aim of this research is to find out the influence of skill learning processes in strategy learnig Student Tem Heroic Leadership by giving structured assigment about result at the students learning in the material circle tangent for class VIII MTs Miftahut Thullab Sukolilo-Pati academic year 2015/2016. The research is a quantitative. The population of this study are all students of class VIII MTs Miftahut Thullab Sukolilo-Pati, it’s consists three classes with 91 students. This research s take off one class at random from threed class. In class VIII A totaling 35 students. The research is to do in three meetings and one meeting for acievement test.  The research data obtained from: (1) observation activity, (2) achievement test. The test use in this research is linear regression and One sample T-test. The Collecting data using documentation methods, observation methods, test methods and then, firstly doing normality test in the class that will be used for research to find out that the class is normal distribution. The research results to indicated has influnce of skill learning processes in strategy Student Team Heroic Leadership by giving structured assigment about result at the student learning in the material circle tangent at 58% by regression model Y = -34.946 + 2,141x is linear. Result of the average value student is 74,51, in this case the student said to passed the study with suitably miimum learning limit has been set at 70 and the average student learning result is attining good category. The conclussion of the research is skill processes in strategy Student Team Heroic Leadership by giving structured assigment influence on result learinng students inn the class VIII A material circle tangent in the MTs Miftahut Thullab Sukolilo-Pati academic year 2015/2016.